Clinical case of pelvic dystopia of left kidney complicated with terminal hydronephrosis - А.D. Bedeniuk; V.V. Tverdohlib; А.I. Mysak; S. Nesteruk; О.A. Yakymchuk; L.Ye. Viytovych (Вісник медичних і біологічних досліджень, 2022)
Summary. Congenital anomalies of the kidneys and upper urinary tract occupy one of the first places among the defects of various organs and systems, accounting for 13–39 % of all congenital malformations and up to 5 % of the total number of urological patients. The most common types of anomalies are disorders of the location and shape of the kidneys, including: anomalies of renal fusion, renal dystopia. The aim of the study – to shed light on a clinical case involving a rare abnormality in the development of the urinary system, namely pelvic renal dystopia complicated by terminal hydronephrosis. Materials and methods. The patient, who was hospitalized in the Urology Department of Ternopil University Hospital, underwent general clinical, laboratory, radiological and instrumental methods of examination to assess the state of the urinary system. Results. Patient K. applied to the Ternopil University Hospital with complaints of recurrent paroxysmal pain in the suprapubic area, frequent urges to urinate, which appeared during the last two weeks. At objective physical inspection it is revealed a tumor-like formation above the womb, which deformed the anterior abdominal wall. Laboratory parameters – general, biochemical blood tests, coagulogram and electrocardiogram – without pathological changes. According to the ultrasonographic examination of the abdomen and retroperitoneal organs in the projection of the bladder there is an anechoic formation of 220 x 110 cm with a homogeneous content and a wall of 5 mm. The left kidney is not defined. Excretory urography was performed, as a result of which the absence of contour, function of kidney, deformation of the bladder were revealed. As a result of the diagnosis of the disease of this patient it was possible to establish a congenital anomaly of the urinary system, pelvic dystopia of the left kidney complicated with terminal hydronephrosis, which caused compression of the bladder, which, in fact, was the reason for frequent calls to urinate. Conclusions. The results of the analysis of modern world literature show that although the anomalies of the urinary system are among the first congenital malformations of various organs and systems, and renal dystopia is observed in almost 0.24 % of the population, pelvic dystopia complicated by terminal hydronephrosis occurs only in 0.0095 %. Thus, it can be argued that pelvic dystopia complicated by terminal hydronephrosis is a clinical case that is very rare